PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 028 SERUSA - Muslihah '; Mahmud alpusari; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this Class Action Research is how the application of Cooperative Learning Model Make A Match in improving learning outcomes IPS third grade students of SD Negeri 028 serusa. For that we need to be improved in order to improve learning outcomes. Efforts to repair is done by applying Cooperative Learning Model Make A Match. Research conducted in the third grade elementary school serusa 028, with the number of students 20 students consisting of 10 male students and 10 female students. Data collection techniques were used that observation techniques and test engineering. Data analysis technique used is the result of learning, completeness individual and classical, the activities of teachers and students, individual awards. The results showed that the initial data is known that the students' social studies students only in average 60.4 and completeness achieved by 45% with less category. In the first cycle and the class action after being evacuated there was little increase student learning outcomes IPS with an average of 69.5 and classical completeness is still reaches 70% with both categories. Seeing the conditions achieved in the first cycle of meetings 1 and 2, the researchers took the initiative to proceed to the second cycle. After learning social studies carried out in this second cycle learning outcomes achieved by students which averaged 80.0 and classical completeness of 100% with a very good category. This means that the Cooperative Learning Model Make A Match is one of the effective learning methods to improve learning outcomes IPS grade II SD Negeri 028 Serusa, Bangko Subdistrict, Rokan Hilir.Keywords : Cooperative Learning Model Make A Match, IPS Learning Outcomes